ELECTROLYTE USED IN COMPLEX EROSION PROCESS - KAOLIN - Alin NIΟAŢĂ (Fiabilitate şi Durabilitate)
The kaolin is part of the clayey suspension, which may be used as working environments through complex electrical erosion. Within these suspensions forming the passive film is explained through electrophoresis when a process of migration of the particles charged electrically toward one of the electrodes under the action of the electrical field takes place. Forming the passive film takes place because of the colloidal micelles resulted through the dissociation of the kaolin, which due to their negative charge, they are fixed on the anode, through forces of absorption. Because these forces are weak, the film has a low adherence and it does not protect correspondingly the piece favouring the electrical discharge in more than one point.